2014/15 Average Packing Charges for Florida Fresh Citrus - Ariel Singerman (EDIS, 2016)
A survey of Florida fresh citrus packers was conducted in April 2015 to collect data on their packing charges during the 2014/15 season. A total of sixteen packinghouses participated in the survey, seven from the Interior region and nine from the Indian River region. The average of their responses was computed to obtain the estimates presented in this document.